“Droit européen“ à la liberté religieuse et paradigmes des relations État- religions dans l’Europe contemporaine: une cacophonie épineuse (Stato, Chiese e pluralismo confessionale, 2021)
SOMMAIRE: 1. Introduction: paradigmes de relations et droit à la liberté religieuse, de l’identité à la tension - 2. Des paradigmes des relations État-Églises au droit à la liberté religieuse - 3. La force attractive des paradigmes dans le scénario européen contemporain - 4. Les paradigmes des relations État-Églises dans la nouvelle arène internationale - 5. Conclusion: une citoyenneté inachevée.The “European Right” to Religious Freedom and Paradigms of State-Religion Relations in Contemporary Europe: a thorny cacophonyABSTRACT: The article examines the dialectic between European national models of religious freedom and the paradigm of religious freedom shaped in the international order and in particular by the human rights discourse. The analysis of the relationship between the modern - national-centered - and the contemporary - individual-centered - paradigm of religious freedom reveals, on the one hand, the difficult but inevitable osmosis between legal systems in a multilevel system of rights protection and, on the other hand, the deep transformation of religious freedom in contemporary Europe.